Literature Review : Effect of Static Conditions on Musculoskeletal Disorders (MSDs) - Diana, Venny (Basic and Applied Nursing Research Journal, 2021)
Musculoskeletal disorders are disorders that occur in one of the skeletal organs or muscles of the body such as congenital abnormalities in the upper and lower extremities, nerve and muscle disorders, inflammatory infections of bones and joints, musculoskeletal metabolic disorders, degenerative musculoskeletal disorders (spine, upper extremities) and below). The study aimed To analyze the static condition of the workers' complaints of musculoskeletal disorders (MSDs). Using literature review with scoping review method. The data was collected through internet searches using Google Scholar and PubMed with the keywords static conditions, complaints of MSDs, ergonomic position, musculoskeletal disorders, the influence of static conditions, with a range of research years is 2015-2020. Results found 83 articles matching the keyword. A review of 9 research articles that met the inclusion criteria found 4 aspects, namely the factor of length of work more than 1 year, age, working hours and using the same extremity for a long period of time will increase the risk of MSDs, Doing work in awkward positions for 5- 8 hours/day increases the risk of MSDs in workers, especially nurses, The emergence of MSDs symptoms is higher in women, namely in the lower back and neck area, The pain felt due to MSDs disorders can be severe, namely in the lower back, shoulders, neck, wrists , knees and ankles. There is a relationship with static positions/non-ergonomic conditions at work, these non-ergonomic conditions do not directly cause complaints but in the long term complaints will arise. The female gender is at high risk of experiencing MSDs, the length of work and length of time working will affect the emergence of MSDs, there are 12 static conditions found in someone when doing work, the main complaint that appears in MSDs is pain.